2008
DOI: 10.1123/jpah.5.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Associations Between Church-Based Social Support and Physical Activity

Abstract: Objective:This study tested associations between church-based instrumental and informational social support and meeting physical activity guidelines.Methods:Cross-sectional data were analyzed for 1625 rural residents using logistic regression.Results:Associations were found between instrumental social support and performing some amount of physical activity but not between the 2 forms of support and meeting physical activity guidelines.Conclusion:Instrumental social support might help initiation of physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 27 publications
(23 reference statements)
1
43
0
Order By: Relevance
“…With regard to physical activity, individuals who reported receiving informational religious support (e.g. receiving physical activity information from clergy), were more likely to meet recommended physical activity guidelines (Kanu et al, 2008). Church-based emotional support was associated with lower risk of mortality among older adults, and helped individuals to deal with financial strain (Krause, 2006a).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…With regard to physical activity, individuals who reported receiving informational religious support (e.g. receiving physical activity information from clergy), were more likely to meet recommended physical activity guidelines (Kanu et al, 2008). Church-based emotional support was associated with lower risk of mortality among older adults, and helped individuals to deal with financial strain (Krause, 2006a).…”
mentioning
confidence: 98%
“…Because faith-based organisations typically consist of individuals similar in backgrounds and values, social networks thrive in these settings (Ellison & George, 1994). Social support specifically in the context of the faith-based setting, such as that provided by clergy and congregation members, is referred to as religious social support or religious support (Kanu, Baker, & Brownson, 2008). Like general social support, religious support is also thought to be multifactorial, and can include dimensions such as emotional support, anticipated support and negative aspects of social interactions (Krause, Ellison, Shaw, Marcum, & Boardman, 2001).…”
mentioning
confidence: 99%
“…Kanu, Baker, & Brownson (2008) found no association between church-based informational (e.g. “does your church ever include health messages about PA in the church bulletin distributed during weekly services?”) or instrumental (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…Diet is influenced by a range of environmental factors, including social support (Bandura, 1986;Booth, et al, 2005;Thornton, et al, 2006); therefore, confidence in overcoming the barriers to healthy dietary behavior could be influenced by social support and other means of affective reinforcement (Bandura, 1986;Sheeshka et al, 1993). Several studies have shown that social support is associated with healthy behaviors such as smoking cessation (Wagner et al, 2004;Turner et al, 2008;Vaananen et al, 2008;Lawhon et al, 2009), reducing alcohol consumption (Steptoe et al, 1996;Hagihara et al, 2003), increasing physical activity (Spanier et al, 2001;Okun et al, 2003;Anderson et al, 2006;Kanu et al, 2008), and cancer screening (Seow et al, 2000;Katapodi et al, 2002). These studies have found that people with a high level of social support were more likely to quit risky health behaviors and engage in health-promoting behaviors.…”
Section: Introductionmentioning
confidence: 99%